A STUDY OF WOMEN'S LANGUAGE VARIETIES USED BY BRITTANY HIGGINS IN ABC NEWS YOUTUBE CHANNEL - Khatima, Khusnul; Nur, Sahril; Nur, Muh Safar (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research discusses the use of women's language varieties by Brittany Higgins in ABC News YouTube channel. The researchers selected Brittany Higgins as object of the research because women's language can be observed to reflect women's lives in various social situations. The aim of this research is to identify the types and functions of women's language used by Brittany Higgins to emphasize and strengthen her speech. This research employs the theory types of women's language proposed by Lakoff (1975) and explains the functions of each type of women's language used by Brittany Higgins based on the language function theory by Jakobson (1896-1982). The research method used is descriptive qualitative to identify and explore the varieties of women's language used by Brittany Higgins in the ABC News YouTube channel. The research data is taken from the speech transcripts and conversations of Brittany Higgins during the National Press Club 2022 in ABC News YouTube channel. The research result showed that there are seven types of women's language used by Brittany Higgins out of the ten proposed by Lakoff (1975). These varieties include the use of lexical hedges/fillers (25.73%), rising intonation (10.58%), empty adjectives (4.56%), intensifiers (25.00%), Hypercorrect grammar (12.04%), avoidance of strong swear words (0.55%), and emphatic stress (21.53%). Additionally, the researchers found all the functions of women's language within the variations used by Brittany Higgins, with the emotive function being the most dominant with an exclusive style.